FACILITATING LEARNING STYLES IN ELEMENTARY SCHOOL STUDENTS - Widia Indra Kartika; Syifa Lailatul Mutmainnah; Nurlia Agustina; Moh Salimi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Educators need to understand student learning styles so that the delivery of material or the learning process becomes smooth and successful. Educators need to understand also ways to facilitate students according to learning styles. The purpose of this study is to (1) describe student learning styles; (2) describe ways to facilitate student learning styles. The results of this study are: (1) learning style is a learning process of students in accordance with their skills and abilities which consist of visual learning styles, auditory learning styles, and kinesthetic learning styles. (2) ways to facilitate visual learners through vision or depiction, auditory learners learn through hearing, and kinesthetic learners learn through motion or touch.